Pengaruh Kompleksitas Tugas dan Self-Efficacy terhadap Audit Judgment dengan Gender sebagai Variabel Moderasi - Prameswari, Desty Villa (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2025)
This study aims to examine the factors influencing audit judgment among auditors at the Inspectorate of West Kalimantan Province and the Inspectorate of Kubu Raya Regency by analyzing the effects of task complexity and self-efficacy with gender as a moderating variable. This research employs a quantitative approach with a causal comparative research design. The data used in this study are primary data collected through questionnaires distributed to auditors. The population consists of all auditors working at the Inspectorate of West Kalimantan Province and the Inspectorate of Kubu Raya Regency, with a final sample of 43 respondents. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach using WarpPLS 8.0 software. The results indicate that task complexity has a positive effect on audit judgment, self-efficacy has a positive effect on audit judgment, and gender moderates the relationship between task complexity and audit judgment as well as the relationship between self-efficacy and audit judgment. These findings suggest that individual factors and situational factors play an important role in shaping auditors’ judgment processes, particularly in government audit environments.